The Influence Of Principal Leadership, Supervision, And Motivation On Teacher Discipline At SMAN 01 Central Bengkulu - Muhammad, Muhammad; Indriasari , Nia; Putra , Iswidana Utama (Jurnal Bisnis, Manajemen dan Akuntansi, 2026)
provide direction and guidance in teaching activities to create a character-based environment. The purpose of this study was to determine the influence of leadership, supervision and motivation of the principal on the work discipline of teachers at SMAN 01 Bengkulu Tengah. The sample in this study was 54 civil servant teachers at SMAN 01 Bengkulu Tengah, data collection using questionnaires and the analysis methods used were multiple linear regression, determination test and hypothesis test. The results of multiple linear regression show the equation Y = 2.579 + 0.608X1 + 0.735X2 + 0.807X3 + 1.018 (e) the direction of the resulting regression is positive so that it means that the increasing the variables of leadership, supervision and motivation, the work discipline will also increase. The determinant coefficient value is 0.971. This means that X1 (leadership), X2 (supervision), X3 (motivation) have a contribution to work discipline (Y) of 97.1% while the remaining 2.9% is influenced by variables outside the study, the results of the t test have a significant value of less than 0.05, so it can be interpreted that X1 (leadership), X2 (supervision), X3 (motivation) have a significant influence on work discipline (Y) partially or individually. The results of the f test have a significance value of 0.000 <0.05. Because the significance level is below 0.05, it shows that together X1 (leadership), X2 (supervision), X3 (motivation) have a significant influence on work discipline (Y).